KARAKTERISTIK KLINIS DAN FAKTOR KOMORBID PASIEN COVID-19 di RSUP DR. M. DJAMIL PADANG - Rosmaini Rosmaini; Maharani Syair; Bun Yurizali; Suharni Suharni (Yayasan Nusantara Hasana Berdikari, 2023)
Coronavirus disease 2019 (COVID-19) is a potentially fatal infectious disease caused by a novel coronavirus (nCoV), Severe Acute Respiratory Syndrome Corona Virus 2 disease (SARS-CoV-2).Because the information is transmitted from person to person, the process is very quick.Passien comorbidity factor can reduce the likelihood of COVID-19 infection. The purpose of this study is to learn about the clinical characteristics and risk factors for COVID-19 at RSUP Dr. M. Djamil Padang in 2021. There is 97 people were sampled using the purposive sampling technique. The clinical symptom characteristics of COVID-19 patients were dominated by fever (69.1%) and shortness of breath (61.9%); signs were dominated by respiratory frequency 30x/minute (76.3%); and comorbid factors were dominated by hypertension (66%) and diabetes mellitus (64.9%). The clinical characteristics of COVID-19 patients at Dr. M. Djamil Padang's clinic in 2021 are dominated by symptoms (fever and shortness of breath), signs (respiratory rate 30x/minute), and comorbid factors (hypertension and diabetes mellitus.